PENGENALAN DASAR PEMROGRAMAN PYTHON UNTUK SISWA MAN 1 BANYUMAS MELALUI PLATFORM CODECOMBAT - Ghilman Yahya Purnama; Aditya Imam Putra Kusuma; Dzikri Kridantama; Ikbal Fauzi; Yosep Oktavianus Teguh; Darso Darso (CV. Denasya Smart Publisher, 2026)
This community service activity consisted of a workshop introducing basic Python programming to 24 students of MAN 1 Banyumas using the CodeCombat platform. The workshop was held on May 13, 2026, in the computer laboratory of MAN 1 Banyumas, lasting 2.5 hours. CodeCombat is a game-based learning platform that enables students to learn programming languages interactively and engagingly without any prior coding background. The workshop was divided into three sessions: an introduction to Python concepts, hands-on coding practice on CodeCombat, and a top-leaderboard competition with prize distribution. Results showed that 23 out of 24 participants (95.8%) successfully completed at least one level, with an average of 8.4 levels per active participant. The top performer completed 16 levels and mastered six Python concepts within a single session. Based on evaluation forms completed by 17 respondents, all provided positive feedback, with 52.9% reporting being Very Satisfied and 47.1% reporting being Satisfied. CodeCombat proved effective as a game-based coding introduction medium for madrasah students with no prior programming experience.